Photostabilization of Phenoxyacetic Acid Herbicides MCPA and Mecoprop by Hydroxypropyl-β-cyclodextrin - Cátia Costa; Sílvia Maia; Paulo Silva; Jorge Garrido; Fernanda Borges; E. Manuela Garrido (International Journal of Photoenergy)
New strategies to reduce the environmental and economic costs of pesticides use are currently under study. Microencapsulation has been used as a versatile tool for the production of controlled release agricultural formulations. In this study, the photochemical degradation of the herbicides MCPA and mecoprop has been investigated in different aqueous media such as ultrapure and river water under simulated solar irradiation. To explore the possibility of introducing cyclodextrins in the herbicide formulations, the photodegradation study of the inclusion complexes of MCPA and mecoprop with (2-hydroxypropyl)-β-cyclodextrin (HP-β-CD) was also performed. The half-lives of MCPA and mecoprop inclusion complexes were increased approximately by a factor of three related to the free molecules. Additionally, it has been shown that the photodegradation of MCPA and mecoprop is influenced by their structural features. The additional methyl group existing in mecoprop molecular structure has a positive influence on the stabilization of the radical intermediate formed in the first stage of photodegradation of both herbicides. The results found indicated that MCPA and mecoprop form inclusion complexes with HP-β-CD showing higher photostability compared to free herbicides indicating that HP-β-CD may serve as ingredient in these herbicide formulations.